PENGARUH SUBSTITUSI TERIGU DENGAN BUAH LINDUR (Bruguiera gymnorrhiza L.) TERHADAP KARAKTERISTIK FLAKES - Aldila Prianggi, Desty; Widpradnyadewi, Putu Ari Sandhi; Wisaniyasa, Ni Wayan (Jurnal Ilmu dan Teknologi Pangan (ITEPA); Vol 5 No 2 (2016): Jurnal ITEPA)
The aims of this research is to determine the substitution effect of wheat with lindur fruit ( Bruguiera gymnorrhiza L.) againts to the characteristics of the flakes, and to know the comparison lindur fruit and wheat that produce flakes with the best characteristics. This research used completely randomized design with the comparison of wheat with lindur fruit treatments, there are : 100% for wheat with 0% for pulp lindur, 85% for wheat with 15% for pulp lindur, 70% for wheat with 30 % for pulp lindur, 55% for wheat with 45% pulp lindur, and 40% for wheat with 60% for pulp lindur. Each treatment was repeated 3 times to obtained 15 experimental units. Data being acquired would be analyzed with variance analysis and if there was an effect to the variables being examined, then it would be continued with Duncan test. The result of research showed that the ratio between 40% wheat flour and 60% lindur fruit resulted in the best flakes characteristic with water content of 5.18%, ash content of 2.57%, protein content of 5.25%, fat content of 9.66%, carbohydrate content 77.38%, crude fiber of 6.07%, tensile strength of 4.52 N, color rather like, texture like, aroma rather like, taste like, and the overall acceptance like.
Keywords: Wheat, Lindur Fruit, Characteristics, Flakes